2022
DOI: 10.3390/foods11030330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathepsins on Gel Strength and Water-Holding Capacity of Myofibrillar Protein Gels from Bighead Carp (Aristichthys nobilis) under a Hydroxyl Radical-Generation Oxidizing System

Abstract: This study investigates the effects of cathepsins on the gel strength and water-holding capacity (WHC) of myofibrillar protein gels from bighead carp (Aristichthys nobilis) under a hydroxyl radical-generation oxidizing system. The myofibrillar proteins were divided into control group (with cathepsins) and E64 group (without cathepsins). The changes of cathepsin B and cathepsin L activities, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), protein oxidation (total sulfhydryl and carbonyl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The protein surface hydrophobicity is closely related to the WHC of protein structure; higher water retention tends to be associated with a higher surface hydrophobicity ( Lee and Chin, 2020 ; Zayas, 1997 ). High hydrophobicity can contribute to improve WHC and GS by binding proteins and stabilizing the three-dimensional structure of gel ( Lu et al, 2022 ). Chen et al (2023) reported that the surface hydrophobicity and WHC of MP extracted from yellow croaker increased with increasing pea protein concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The protein surface hydrophobicity is closely related to the WHC of protein structure; higher water retention tends to be associated with a higher surface hydrophobicity ( Lee and Chin, 2020 ; Zayas, 1997 ). High hydrophobicity can contribute to improve WHC and GS by binding proteins and stabilizing the three-dimensional structure of gel ( Lu et al, 2022 ). Chen et al (2023) reported that the surface hydrophobicity and WHC of MP extracted from yellow croaker increased with increasing pea protein concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effects between MgCl 2 concentration and heating temperature also significantly affect the gel's WHC. As the temperature rises, heat-treated proteins denature, unfold, and expose their internal hydrophobic groups, thereby increasing their affinity for water molecules and ensuring stability during centrifugation ( Lu, Liang, Zhang, & Wen, 2022 ). Moreover, divalent Mg 2+ ions and exposed sulfhydryl groups can form disulfide bonds, producing cross-linking structures, favoring protein aggregation, enhancing interactions between proteins, and between protein and water, and consequently, enhancing the protein network and gel strength.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rinsing process causes nutrient loss, it also imparts some beneficial properties to the gel formation of surimi products. The water‐soluble proteins lost during rinsing include (i) myosin, which binds to myogenic fibronectin and thus interferes with the formation of a firm gel network, resulting in poor gelation of the surimi; 41 (ii) myoglobin and hemoglobin, which affect the appearance and gel quality of the surimi; 42,43 (iii) several proteases that affect the deterioration of surimi during gel formation; 44,45 (iv) some of the proteases that affect the deterioration of gel formation of surimi (proteasome subunit alpha type‐2, 3, 4, 5, 7, low‐molecular‐weight phosphotyrosine protein phosphatase, etc. ); 46,47 and (v) some of the enzymes associated with the oxidation of proteins during storage of surimi (glycogen phosphorylase muscle form, creatine kinase M‐type, pyruvate kinase M, fructose‐bisphosphate aldolase A) 48,49 .…”
Section: Discussionmentioning
confidence: 99%